2002
DOI: 10.1177/009207002236915
|View full text |Cite
|
Sign up to set email alerts
|

Can Price Dispersion in Online Markets be Explained by Differences in E-Tailer Service Quality?

Abstract: It has been hypothesized that the online medium and the Internet lower search costs and that electronic markets are more competitive than conventional markets. This suggests that price dispersion of an item with the same measured characteristics across sellers at a given point in time for identical products sold by e-tailers online should be smaller than it is offline, but some recent empirical evidence reveals the opposite. Based on an empirical analysis of 105 e-tailers comprising 6,739 price observations fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(153 citation statements)
references
References 20 publications
9
141
2
1
Order By: Relevance
“…After having looked into the price data concerning online distribution channel of six pure single-channel and six multi-channel retailers, Tang and Xing concluded that the former are 20-30% lower in price discrimination than the latter. A similar conclusion is found for CDs, books, tapes and household appliances Lu 2001, Pan et al2002) [12,13].…”
Section: Literature Reviewsupporting
confidence: 65%
“…After having looked into the price data concerning online distribution channel of six pure single-channel and six multi-channel retailers, Tang and Xing concluded that the former are 20-30% lower in price discrimination than the latter. A similar conclusion is found for CDs, books, tapes and household appliances Lu 2001, Pan et al2002) [12,13].…”
Section: Literature Reviewsupporting
confidence: 65%
“…On the contrary, there is evidence that contradicts the increasing price competition assumption in e-business (Degeratu, Rangaswamy, & Wu, 2000). Even in e-business, brand-loyal customers are less sensitive to price (Pan, Ratchford, & Shankar, 2002) so that companies with the ability to provide superior product information to build trust and loyalty can counter the price advantage of competitors (Lynch & Ariely, 1998). Moreover, in some cases, including car auction markets (Lee, 1998) and retailing (Bailey, 1998), traditional market prices are lower than online market prices.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…on how shipping options are chosen by retailers. In an investigation of the drivers of on-line price dispersion, Pan et al (2002a) find that the shipping options adopted by retailers contribute significantly to the variation in firms' prices. While this finding hints at the importance of shipping policies in generating variations in price, the direction of the relationship and the channel through which the relationship emerges are left unexplored.…”
Section: Introductionmentioning
confidence: 99%